The Formation of the Budget of Own Resources in the MERCOSUR - A. M. Massalimova (Мир новой экономики)
In article the author describes process forming of own budget MERCOSUR - the total market of the countries of South America, the integration consolidation created in 1991. Members MERCOSUR are Argentina, Brazil, Venezuela, Paraguay and Uruguay now. The sixth country, Bolivia, is in process of accession to the block today. Associated members of consolidation - Guyana, Colombia, Peru, Surinam, Chile and Ecuador. Mexico and New Zealand have the status of observers. The total amount of GDP of the states MERCOSUR in 2014 made 3,2 trillion US dollar. The population of the countries of consolidation totals over 285 million people. In article it is shown how own resources MERCOSUR are created and distributed through system of budgets of various bodies entering into this international organization (Fund of structural convergence MERCOSUR, Social institute MERCOSUR, Parliament MERCOSUR, the Secretariat MERCOSUR, the Secretariat of Fixed auditing court, etc.). Through these budgets financial provision of activities MERCOSUR on economic integration of member countries, including content of bodies MERCOSUR is performed.